Synthesis and Claisen rearrangement of bridged bicyclic enol ethers of relevance to the course of ketene s-cis-diene cycloaddition. - Robertson, J; Fowler, T (2006)
The synthesis is described of a range of 3-alkylidene-2-oxabicyclo[2.2.1]hept-5-ene and 3-alkylidene-2-oxabicyclo[2.2.2]oct-5-ene derivatives; Claisen rearrangement of these substrates either thermally or in the presence of an added Lewis acid results in the formation of bicyclic cyclobutanones with generally good conversions. These reactions may be performed in hydroxylic solvents, supporting a largely non-dissociative pathway for the rearrangement.